2010
DOI: 10.1161/hypertensionaha.110.155556
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 Induces Migration of Monocytes in a Tie-2 and Integrin-Independent Manner

Abstract: Abstract-Angiopoietin-1 (Ang-1) is an angiogenic growth factor that activates Tie-2 and integrins to promote vessel wall remodeling. The recent finding of the potential proatherogenic effects of Ang-1 prompted us to investigate whether Ang-1 promotes monocyte chemotaxis, endothelial binding, and transendothelial migration, key events in the progression of atherosclerosis. Here, we show that Ang-1 induces chemotaxis of monocytes in a manner that is independent of Tie-2 and integrin binding but dependent on phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…45 It has also been reported that Ang1-mediated effects on monocyte adhesion and chemotaxis are both Tie2 and integrin independent. 46 Hence, QHREDGS may bind and promote the survival of cardiomyocytes, cardiac fibroblasts, and endothelial cells through integrin-binding but may not affect monocyte/macrophage function, which would account for the absence of a significant inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…45 It has also been reported that Ang1-mediated effects on monocyte adhesion and chemotaxis are both Tie2 and integrin independent. 46 Hence, QHREDGS may bind and promote the survival of cardiomyocytes, cardiac fibroblasts, and endothelial cells through integrin-binding but may not affect monocyte/macrophage function, which would account for the absence of a significant inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the highly restricted expression of Angpt-1’s receptor, Tie2, to endothelium confers additional cellular specificity to the in vivo results. Nonetheless, Angpt-1 could have acted on putative non-Tie-2 receptors [43], and extra-endothelial effects of p47phox deletion could still have factored into the observed permeability results. [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that the presence of PTK7 itself is responsible for ANG-1 secretion in mononuclear cells. As ANG-1 is a well-known mediator secreted by pericytes to recruit VECs and promote vascular stability, 12, 28 PTK7 + cells may stabilize vessel formation via ANG-1 secretion. Thus, we investigated the functional role of ANG-1 in PTK7 + cells.…”
Section: Resultsmentioning
confidence: 99%
“…28, 4143 ANG-1 expression from BM cells appears to have a critical role in angiogenesis, pericyte recruitment, and vascular stabilization. 12, 28, 44 Our findings show that PTK7 + cells highly express ANG-1 and that the vascular stability of VECs is ANG-1 dependent (Figure 5), suggesting that PTK7 + CD11b + cells supply ANG-1 to the angiogenic area to promote vascularization at an early angiogenic time point.…”
Section: Discussionmentioning
confidence: 99%